Anthropological justification for the study of nursing and complementary and alternative medicines - Daniel Gómez Pérez; Domingo Palacios Ceña (Universidad de Alicante, 2012)
The attention and action in the process of health / disease care is a key that characterizes his role as nurse and health worker. In particular the study of health seeking behavior and observation of the strategies of patients (actors) on health and disease and its action as they or their family sick. This article is a reflection through a review of authors in other anthropological work on the articulation of cultural care in biomedical practice. Biomedicine holistic limited compression of the disease conception of the person as a whole than the sum of the component parts. Often the nurse plays in their practice a moral world of values of the society to which he belongs which is materialized in practice. To discuss the influence of culture in the health / disease / care, we must define what is meant by culture. It must take into account the relationship between subject and culture particularly in relation to the socialization of the subject. Hence the importance of the existence of a shared belief system.